Family stories; Oral tradition, memories of the past, and contemporary conflicts over land in Mentawai - Indonesia - Tulius, Juniator (Wacana, Journal of the Humanities of Indonesia, 2014)
This is a study of oral tradition on Mentawai family stories. The family stories relate to historical events and contemporary social issues occurred in the Mentawai Islands and affecting the Mentawai kin groups. The Mentawai family stories comprise significant elements defining different kin groups living on the Mentawai Islands. They are also an important source of information with regard to claims to ancestral land. The Mentawai family stories can furthermore be regarded as the kin groups' verbal form of identities. Therefore, to maintain the family stories is indispensable to Mentawai communities and the power of human memory plays an important part in maintaining and transmitting the significance of these verbal identities of the communities.